Control Method for Improving Voltage Response and Ripple of Isolated DC-DC Converter - Li, Ming; Wang, Kairang; Zhao, Zhou; Liu, Hongyong; Zhang, Wenyu; Kou, Jian; Meng, Jianhui (Frontiers in Energy Research, 2022)
Affected by the abrupt changes of load and unregulated first-stage rectifiers, it is difficult for the output voltage of the isolated DC-DC converter with traditional proportional-integral (PI) control to meet the needs of industrial applications such as automotive electrophoretic painting. A voltage response improving the method based on a radial basis function neural network (RBFNN) is proposed in this study for the output voltage mutation of DC converter caused by load mutation. By detecting the output voltage deviation and load current value, the RBF model gives the compensation amount of the duty ratio to enhance the PI controller to speed up the voltage regulation and improve voltage response. For the six-pulse voltage ripple introduced by the unregulated rectifier in the previous stage, a delay link is adopted, where the compensation amount of the duty ratio and its delay time are reasonably designed to reduce the ripple value. The experimental test platform is built, and the proposed method is verified. The results show that the proposed method can effectively improve the output voltage response and ripple as well as improve the output voltage quality of the DC converter, which is of certain engineering application value.